Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Does anyone know how to simplify 5y (2y-3)+(2y-3) to get (5y+1)(2y-3) as a answer

Sagot :

      5y(2y - 3) + (2y - 3) = (5y + 1)(2y - 3)
5y(2y) - 5y(3) + (2y - 3) = 5y(2y - 3) + 1(2y - 3)
    10y² - 15y + (2y - 3) = 5y(2y) - 5y(3) + 1(2y) - 1(3)
      10y² - 15y + 2y - 3 = 10y² - 15y + 2y - 3
              10y² - 13y - 3 = 10y² - 13y - 3